“Kebunku” Educational Game Using Construct 2 - Donna Apriana Sari; Yulianto; Nisa Rizqiya Fadhliana (Politeknik Pertanian Negeri Samarinda, 2020)
The sophistication of technology today can provide devices outside of computers, and edited into computers in the form of education. Games that have educational content are better known as educational games. This educational type game aims to provoke children's interest in learning subject matter while playing games, and is not focused on entertainment alone without any educational elements and is a fun learning tool for children aged 7-8 years of elementary school. The development of this game will use construct 2 as a means of making a game. Construct 2 uses the HTML 5 programming language and supports the development of 2-dimensional (2D) applications so that it is considered suitable for use in this game development process. The purpose of this research is to build an application for my Kebunku Educational Game using Construct 2 which is played on a computer and to learn the techniques for making a Kebunku Educational Game using construck 2 by going through three stages, namely the process of planting fruit seeds, watering fruit seeds and picking the fruit harvest. The result of making this game is my Kebunku Educational Game Application Using Construct 2.